(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Hasibuan R, Cindowarni O, Lumbanraja J, Lumbanraja FR. 2022. Impact of soil fertilization on arthropod abundance and diversity on soybean agroecosystem. Biodiversitas 23: 1828-1835. Arthropods are biotic components that play an important role in the ecosystem. The field experiment consisting five fertilizer treatments: 100% NPK, 100% organic fertilizer, 100% NPK and 50% organic fertilizer, 50% NPK and 100% organic fertilizer, and no fertilizer was conducted to study the arthropod abundance and diversity in soybean agroecosystem. Pitfall traps were set up for collecting soil arthropods, while data for foliar arthropods were obtained by visual observation. During the study, the soybean agroecosystem was inhabited by 2756 arthropods that belong to 64 families. The results of arthropod community composition indicated that soil and foliar arthropods were most dominated by Coleoptera and Hemiptera. Predators were the most abundant in pitfall traps and herbivores with a visual inspection. Additionally, predators had the highest number of families. Soil fertilizer treatments had a significant impact on the abundance of foliar arthropods and soil arthropods. The highest numbers of foliar arthropods were found in soybean plants treated by inorganic fertilizer (NPK) either alone or in combination. However, soil arthropods were most abundant in soybean treated by organic fertilizer. The application of organic fertilizers to the soybean agroecosystem was able to increase the diversity of ground-dwelling arthropods and foliage-inhabiting arthropods across sampling periods.